2019
DOI: 10.1016/j.matpr.2019.06.234
|View full text |Cite
|
Sign up to set email alerts
|

The effect of annealing conditions: temperature, time, ramping rate and atmosphere on nanocrystal Cu2ZnSnS4 (CZTS) thin film solar cell properties

Abstract: The eect of annealing conditions : temperature, time, ramping rate and atmosphere on nanocrystal Cu2ZnSnS4 (CZTS) thin lm solar cell properties.', Materials today : proceedings., 18 (2). pp. 473-486.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The other peaks found at 2θ ≈ 18.3°, 23.2°, 33.1°, 37°, 37.9°, 44.95°, 51.05°, 58.85°, 69.1°, 78.7° are associated with the (101), ( 110 The highest-intensity peak at 2θ ≈ 28.55° can correspond to the (112) plane of the tetragonal structure of kesterite CZTS, as well as the tetragonal structure of Cu 2 SnS 3 , cubic or hexagonal structure of ZnS, CuS, and Sn 2 S 3 . The peak at 2θ ≈ 47.45° can belong to the (220) CZTS plane and to the Cu 2 SnS 3 tetragonal structure or cubic structure of ZnS [23][24][25][26]. Since most of the lines belong to the tetragonal kesterite structure CZTS, it can be concluded that the films crystallize in this structure.…”
Section: Resultsmentioning
confidence: 99%
“…The other peaks found at 2θ ≈ 18.3°, 23.2°, 33.1°, 37°, 37.9°, 44.95°, 51.05°, 58.85°, 69.1°, 78.7° are associated with the (101), ( 110 The highest-intensity peak at 2θ ≈ 28.55° can correspond to the (112) plane of the tetragonal structure of kesterite CZTS, as well as the tetragonal structure of Cu 2 SnS 3 , cubic or hexagonal structure of ZnS, CuS, and Sn 2 S 3 . The peak at 2θ ≈ 47.45° can belong to the (220) CZTS plane and to the Cu 2 SnS 3 tetragonal structure or cubic structure of ZnS [23][24][25][26]. Since most of the lines belong to the tetragonal kesterite structure CZTS, it can be concluded that the films crystallize in this structure.…”
Section: Resultsmentioning
confidence: 99%
“…The annealing process plays an important role in CZTS NCs to achieve high-efficiency devices. A high-temperature postdeposition annealing process leads to the recrystallization due to the migration of atoms in the crystal lattice resulting in the reduced density of defects/dislocations, 31 while the surface recrystallization takes place during the cooling cycle. 25 In order to improve the crystalline quality and stoichiometry of CZTS NCs, the as-synthesized NCs were subjected to a sulfurization annealing at a temperature varying from 300 to 550 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure we used has been described in detail previously. 17 Our synthesis temperature, when sulphur is injected, was 225 1C.…”
Section: Nanocrystal Ink Synthesismentioning
confidence: 99%